2012
DOI: 10.1111/j.1582-4934.2011.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of hypoxia‐inducible microRNA‐210 in pre‐eclampsia: new insights into molecular mechanisms for the disease

Abstract: Pre-eclampsia is a leading cause of maternal and foetal morbidity and mortality worldwide. Insufficient uteroplacental oxygenation is believed to be responsible for the disease. However, what molecular events involve in hypoxic responses and how they affect placental development remain unclear. Recently, miRNAs have emerged as a new class of molecules in response to hypoxia. We show here that the expression of microRNA-210 (mir-210) is up-regulated in patients with pre-eclampsia, as well as in trophoblast cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
217
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 206 publications
(233 citation statements)
references
References 47 publications
12
217
1
3
Order By: Relevance
“…miR-210 was found to be upregulated in trophoblast cells cultured under hypoxic conditions, and in pre-eclamptic patients as compared to healthy controls. 91,100 Interestingly, another study found that miR-210 expression under hypoxia can be regulated by the p50 transcription factor, which in turn regulates HIF-1a in the trophoblast cells. 91 Therefore, miRNAs share regulatory pathways with other placental genes that are altered in pre-eclampsia.…”
Section: Microrna Regulation In the Placentamentioning
confidence: 99%
See 4 more Smart Citations
“…miR-210 was found to be upregulated in trophoblast cells cultured under hypoxic conditions, and in pre-eclamptic patients as compared to healthy controls. 91,100 Interestingly, another study found that miR-210 expression under hypoxia can be regulated by the p50 transcription factor, which in turn regulates HIF-1a in the trophoblast cells. 91 Therefore, miRNAs share regulatory pathways with other placental genes that are altered in pre-eclampsia.…”
Section: Microrna Regulation In the Placentamentioning
confidence: 99%
“…91,100 Interestingly, another study found that miR-210 expression under hypoxia can be regulated by the p50 transcription factor, which in turn regulates HIF-1a in the trophoblast cells. 91 Therefore, miRNAs share regulatory pathways with other placental genes that are altered in pre-eclampsia. 91 In addition to miR-210, other important miRNAs including the miR-17-92 family, which is involved in angiogenesis 101,102 and immune cell development, 103 miR-93, miR-205, miR-335, miR-224, miR-424, miR-451 and miR-491 have been found to be differentially expressed in primary human trophoblasts that were exposed to hypoxia.…”
Section: Microrna Regulation In the Placentamentioning
confidence: 99%
See 3 more Smart Citations